EXPERIMENTING WITH MEDIA EDUCATION, CIVIC ENGAGEMENT, AND SUSTAINABILITY IN BRAZILIAN SCHOOLS - Siqueira, Alexandra Bujokas de; Berardi, Andrea; Mistry, Jayalaxshmi; Rothberg, Danilo [UNESP]; Robinson, L.; Schulz, J.; Dunn, H. S. (Emerald Group Publishing Ltd, 2017)
Purpose - This paper presents the results of research carried out by the Media Education for Sustainability Project, based at the Federal University of Triangulo Mineiro (UFTM). The project investigated the potential for engaging marginalized communities with educational centers to generate and utilize media and networks, which can be used to promote healthier and resilient lifestyles in the community. Methodology/approach - The project's activities used the Design of Meaning theoretical framework to design collaborative group work in order to foster key skills for promoting agency and awareness of local problems affecting the environment. Underpinned by Action Research methodology, a series of workshops were piloted with the participation of 20 secondary school students. Findings - Results suggested that such a creative learning environment can help students develop the skills needed to be active citizens, such as the ability to access, evaluate, use, and contribute to public information addressing issues of democratic participation and accountability. Nevertheless, challenges centered around student motivation and difficulties in engaging with their communities' contexts will need to be dealt with in future Action Research cycles. Originality/value - Based on our observations during the workshops, and subsequent feedback from participants, we suggest that Media Education tools show potential for improving school learning, encouraging the community in the search for answers based on local knowledge, and engaging students in a debate about critical issues and challenges at the local level. We believe that this outcome was achieved in part due to the deployment of multimodal languages and creative use of technologies.
Keywords: Citizenship; sustainability; media education